Islamic bond market: An option to investors - Mohamed Yusoff, Zuryati (Penerbit Universiti Utara Malaysia, 2004)
Islamic Bond Market refers to the market where the activities are carried out in ways that do not conflict with the conscience of Muslims and the religion of Islam. It is the transaction where the market should befreefrom the involvement ofprohibited activities by Islam as well as from the elements such as usury (riba), gambling (maisir) and ambiguity (gharar). Today, Islamic Bond Market plays an important role in generating the economic growth of the country. This article will discuss the types of Islamic bonds, its operation, advantages as well as its unique features that attract investors at large.